2020
DOI: 10.21037/jtd-20-659
|View full text |Cite
|
Sign up to set email alerts
|

Predicting malignancy: subsolid nodules detected on LDCT in a surgical cohort of East Asian patients

Abstract: Background: Due to widespread use of low-dose computed tomography (LDCT) screening, increasing number of patients are found to have subsolid nodules (SSNs). The management of SSNs is a clinical challenge and primarily depends on CT imaging. We seek to identify risk factors that may help clinicians determine an optimal course of management. Methods: We retrospectively reviewed the characteristics of 83 SSN lesions, including 48 pure groundglass nodules and 35 part-solid nodules, collected from 83 patients who u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 34 publications
3
9
0
Order By: Relevance
“…Patients with LAC had a higher age of onset than tuberculosis patients, which could be caused by decreased immunity, cell damage caused by long-term chronic disease, or an increased risk of genetic errors in the old. Malignant nodule was more likely to have a lobulated sign because of invasive growth of malignant cells in the pulmonary interstitium, which was consistent with previous research ( 26 , 27 ). Vacuole sign refers to the presence of a small air-like low-density shadow within the nodule with smooth edges and no more than 5 mm.…”
Section: Discussionsupporting
confidence: 92%
“…Patients with LAC had a higher age of onset than tuberculosis patients, which could be caused by decreased immunity, cell damage caused by long-term chronic disease, or an increased risk of genetic errors in the old. Malignant nodule was more likely to have a lobulated sign because of invasive growth of malignant cells in the pulmonary interstitium, which was consistent with previous research ( 26 , 27 ). Vacuole sign refers to the presence of a small air-like low-density shadow within the nodule with smooth edges and no more than 5 mm.…”
Section: Discussionsupporting
confidence: 92%
“…d VR image shows that the lesion is located among the blood vessels (white arrows). GGO, ground-glass opacity; mGGO, mixed ground-glass opacity; VR, volume rendering [23][24][25][26][27][28][29]. In this study, malignant GGOs were also more frequently found in old and female patients.…”
Section: Discussionsupporting
confidence: 52%
“…Previous studies found that the lesion size was a good indicator of malignant GGNs or invasiveness [1,19,20,23,[31][32][33]. Smaller nodules are commonly benign, while larger ones tend to be malignant [1,19,23,31].…”
Section: Discussionmentioning
confidence: 99%
“…As previous research proved that LDCT has a very good ability in the identification of lung lesions [Error! Bookmark not defined., 23,24] . And in our study, LDCT has a thinner scan thickness, and its resolution is higher than that of CT and PET images, so it can display more details, and extracting an modeling better of radiomics features.…”
Section: Discussionmentioning
confidence: 99%